Spiritual rationality papal embargo as cultural practice - Stantchev, Stefan K. (Oxford University Press, 2014)
Offers the first book-length study of the Roman Catholic church's practice of embargoing trade outside of Christendom in the period c. 1150 to c. 1550, particularly examining the influence of the papacy on the state.